MEMBINGKAI KEMBALI MEMORI SEBAGAI UPAYA MEMBANGUN PEMULIHAN HOLISTIK - Brela Agnesia Maindoka; Hendry C.H Runtuwene (ATOHEMA: Jurnal Teologi Pastoral Konseling, 2026)
This article aims to discuss how humans can avoid trauma from the bad experiences they encounter in life, which can lead to a decline in mental health and disrupt the human mind. In human life, one cannot escape various kinds of incidents, such as the loss of a loved one in a tragic way, being robbed, accidents, bullying, and many more. By reframing memories or events that have occurred, it can be the most effective way to build holistic recovery. Because the recovery process from trauma requires methods that are considered appropriate and suitable, such as psychological approaches, which can help reduce trauma and build resilience. Therefore, this research aims to analyze how recalling memories can help people make peace with those memories, through photos, videos, and perhaps places that were once visited together.